New product announcements, innovation disclosure, and future firm performance - Chu, Jenny; He, Yuan; Hui, Kai Wai; Lehavy, Reuven (Review of Accounting Studies, 2025)
Abstract This study examines the properties of innovation disclosures contained in new product announcements, a form of voluntary, nonfinancial disclosure. We analyze these properties using a novel, text-based measure of the extent of product innovation disclosed in new product announcements. We find that stock prices react more positively to announcements with more extensive innovation disclosure. In our main analyses, we first find that a higher level of innovation disclosure predicts a greater increase in future sales. We further find that this predictive ability falls when managers have stronger incentives to maximize their wealth and when the corporate governance structure and customers’ bargaining power weaken. Our research enhances the understanding of the properties of managerial voluntary, nonfinancial disclosures and contributes a text-based measure of innovation that captures managerial assessment of the extent of product innovation. This new measure is more generalizable and incrementally informative for firm value and future performance than conventional innovation measures that depend on the existence of patents or research and development expenses.